Role 1 Pediatric Trauma Care on the Israeli–Syrian Border—First Year of the Humanitarian Effort. Issue 8 (1st August 2016) - Bitterman, Yuval; Benov, Avi; Glassberg, Elon; Satanovsky, Alexandra; Bader, Tarif; Sagi, Ram
ABSTRACT: Background: This article summarizes the experience with Role 1 care for 135 Syrian children who received medical care during the year 2013 as part of an ongoing humanitarian effort. Methods: The database included demographic information, point-of-injury assessment and outcome, and was analyzed using SPSS. Results: Trauma casualties were the majority of the group (84 cases), and mostly male. Almost one-third of casualties arrived more than 6 hours after injury, and time of injury was unknown in another third. The most common mechanism of injury was shrapnel (51.2%), followed by gunshot wounds (22.6%). Gunshot wound victims were significantly older than shrapnel and artillery victims ( p < 0.01, < 0.05, respectively). Only 14 cases (14.28%) underwent previous interventions in Syria. Most of the casualties (44 cases, 52.4%) underwent at least one procedure during Role 1 treatment with a high overall success rate (93.18%) that was not correlated to Advanced Life Support provider type (physician [MD], emergency medical technician-paramedic, or both). Mortality was low (3 cases). Conclusion: The study cohort exhibits several unique features, including a delay in arrival to medical care, paucity of prior care and information, and the specific mechanisms of injury. Our study suggests that Advanced Life Support providers do not differ significantly in Role 1 treatment choices and procedure success.